Model Penawaran Dan Permintaan Bawang Putih Indonesia: Pendekatan Sistem Dinamik - Jihan Zakia Adila; Andriyono Kilat Adhi; Rita Nurmalina (Forum Agribisnis, 2023)
There is a reasonably high gap between the ability to supply garlic and demand that requires the government to carry out a garlic import policy to meet domestic needs. The high dependency on imported garlic supplies has caused garlic imports to increase. This study aims to analyze the supply and demand model for garlic and formulate policy recommendations regarding the supply and demand for Indonesian garlic using system dynamics model approach. The model in this study is simulated for the next 12 years (2022-2033). Based on the model simulation results, in the base conditions (before the scenario was implemented), the behavior pattern of garlic availability was goal-seeking. At the same time, demand had an exponential growth behavior pattern, and supply had an increasing trend. In 2033, it is estimated that the availability of garlic will experience a deficit, and garlic production and total farmers' income will continue to decline. Therefore, policies are needed to increase garlic farmers' availability, production, and total income in Indonesia through several policy scenarios. The policy scenario with the best results is a combination of an increase in area, productivity, and the realization of mandatory planting by importers because it can produce the highest availability and production of garlic compared to other scenarios. The most sensitive variable to the availability of Indonesian garlic is mandatory planting. Each increase in the realization of mandatory planting by importers by 10 percent can increase the availability of Indonesian garlic by 4.7 percent.